Constitutively active Artemis nuclease recognizes structures containing single-stranded DNA configurations - Pannunzio, Nicholas R.; Lieber, Michael R. (DNA repair, 2019)
•Expression of constitutively active Artemis-413 increases recombinogenic deletions.•Topoisomerase mutations result in an Artemis-413-dependent increase in recombination.•Dividing cells are more sensitive to topoisomerase loss and Artemis-413 expression.•Artemis-413 expression prevents recombination following camptothecin treatment. The Artemis nuclease recognizes and endonucleolytically cleaves at single-stranded to double-stranded DNA (ss/dsDNA) boundaries. It is also a key enzyme in the non-homologous end joining (NHEJ) DNA double-strand break repair pathway. Previously, a truncated form, Artemis-413, was developed that is constitutively active both in vitro and in vivo. Here, we use this constitutively active form of Artemis to detect DNA structures with ss/dsDNA boundaries that arise under topological stress. Topoisomerases prevent abnormal levels of torsional stress through modulation of positive and negative supercoiling. We show that overexpression of Artemis-413 in yeast cells carrying genetic mutations that ablate topoisomerase activity have an increased frequency of DNA double-strand breaks (DSBs). Based on the biochemical activity of Artemis, this suggests an increase in ss/dsDNA-containing structures upon increased torsional stress, with DSBs arising due to Artemis cutting at these ss/dsDNA structures. Camptothecin targets topoisomerase IB (Top1), and cells treated with camptothecin show increased DSBs. We find that expression of Artemis-413 in camptothecin-treated cells leads to a reduction in DSBs, the opposite of what we find with topoisomerase genetic mutations. This contrast between outcomes not only confirms that topoisomerase mutation and topoisomerase poisoning have distinct effects on cells, but also demonstrates the usefulness of Artemis-413 to study changes in DNA structure.